'A COMPARISON OF FINANCIAL PERFORMANCE AND INVESTMENT STYLES FOR SOCIALLY RESPONSIBLE AND CONVENTIONAL INVESTMENT INDICES IN THE UNITED STATES' - Amish, Patel (2013)
This paper investigates comparing the financial performance for socially responsible investment equity indices and conventional investment equity indices in the United States, accounting for the recent financial crisis. Two conventional indices are used as a benchmark to four socially responsible indices. The conventional indices used in this paper are the S&P500 Index and CRSP Total Market Index. The socially responsible indices used are the Calvert Social Index, FTSE4Good U.S. Select Index, FTSE4Good U.S. 100 Index and the MSCI KLD 400 Social Index. The time period for this investigation is from 2nd January 2001 to 25th June 2013. There is one primary objective and two minor objectives. To obtain results for the primary objective, we first must obtain results for minor objective 1.